Carbon coated NiSe 2 Composite nanomaterials and their preparation methods and applications
The chemical vapor phase transport method mixed with selenium powder and nickel acetylacetonate under vacuum environment to prepare carbon-coated NiSe2 composite nanomaterial, which solved the problems of low purity, uneven particles and unstable in the existing NiSe2 preparation methods, and achieved an efficient and low toxic preparation process to obtain a photocatalyst with excellent performance.
Patent Information
- Application Number
- CN202211542663.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-02
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-12-02
AI Technical Summary
The existing NiSe2 preparation method has many disadvantages, such as the gas phase method is carried out at high temperature and is easy to produce intermediate products, the liquid phase method and solid phase method produce low purity and uneven particles, and NiSe2 itself is unstable, and there is a lack of simple and low-toxic processes to prepare NiSe2@C photocatalyst with excellent performance.
The chemical vapor phase transport method was used to mix selenium powder and nickel acetylacetonate for reaction under vacuum to prepare carbon-coated NiSe2 composite nanomaterial in one step. This method selects selenium powder as the low-toxic selenium source and nickel acetylacetonate as the nickel source and carbon source. By optimizing reaction conditions (such as temperature, time, and vacuum) to obtain NiSe2@C material with good structural uniformity and stability.
The process is simplified and the cost is reduced. The obtained carbon-coated NiSe2 composite nanomaterial has high purity, uniform structure and good environmental stability, and is suitable for the preparation of photocatalysts with excellent performance.
Smart Images

Figure CN115959634B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a carbon-coated NiSe2 material, in particular to a carbon-coated NiSe2 composite nano material and a preparation method and application thereof, belonging to the technical field of nano-carbon material preparation. Background Art
[0002] NiSe2 is a Pauli paramagnetic metal with low resistivity, and its metallic abundance makes it very attractive for energy conversion. Nickel-based chalcogenides have rich valence states and unique electronic structures, resulting in a variety of different phase structures. At the same time, selenides have high conductivity characteristics, which makes NiSe2 have potential applications in energy storage and conversion fields such as batteries and electrocatalysts. It is reported that NiSe2 is an efficient electrocatalyst that can be used for platinum-free counter electrodes and energy storage materials for dye-sensitized solar cells. Its potential use as a HER catalyst has also been studied, and it was found that NiSe2 catalysts perform well in HER in acidic electrolytes and show extremely strong stability.
[0003] Selenium sources for preparing selenides include selenium powder, which is not easily soluble in water and ethanol. Other selenium sources include soluble sodium selenite, selenium dioxide, selenourea, etc. However, other selenium sources except selenium powder are highly toxic and very dangerous to use. Selenium powder is relatively safe in a solid state, and selenium vapor is somewhat toxic. Insoluble selenium powder usually needs to be accompanied by a large amount of reducing agent during use, such as hydrazine hydrate, ethanolamine, sodium borohydride, oleylamine, etc., or the selenium powder is disproportionated using a hot solution of sodium hydroxide. Relatively speaking, it is more environmentally friendly not to use a reducing agent. Sodium selenite and selenium dioxide also need to use a reducing agent, but they are more often used in the electrodeposition method. Under acidic or alkaline conditions, they are deposited on a conductive substrate by a constant voltage or constant current method. Selenium powder is usually obtained by electrolysis of anode mud and is at the upstream of selenium chemical products. The industry first prepares elemental selenium and then converts it into other available selenium sources. The scheme of synthesizing transition metal selenides using selenium powder is relatively safer and can also reduce production costs. At present, there are many methods for preparing selenides, and the most commonly used is the hydrothermal method. This method usually requires the addition of a certain reducing agent, first pre-reacting the selenium powder with the reducing agent, or evenly mixing the water-soluble selenium source with the reducing agent, and then placing it in a reactor to react at a certain temperature. The advantages of this method are that it is conducive to the growth of crystals, less agglomeration, and low energy consumption, but the reaction cycle is long and it relies on instruments and equipment under high temperature and high pressure. The second is the sintering method. Since selenides are easily oxidized in the air, they must be calcined in an inert environment or a reducing atmosphere in a tubular furnace. The calcination method can be used for large-scale production, but it is usually more expensive, the particles are easy to agglomerate, and the operation is relatively cumbersome. In addition, there are methods such as electrodeposition, oil bath and microwave, which still need to be developed and improved.
[0004] At present, the preparation methods of NiSe2 mainly include gas phase method, liquid phase method and solid phase method (such as CN110823971A). Although these methods can well control the composition and morphology of the material and are easy to operate, they also have many disadvantages. For example, the gas phase method is carried out at high temperature, and there is oxygen in the reaction system, which is likely to generate many intermediates including oxides; the products generated by the liquid phase method and the solid phase method have low purity and uneven particles. At the same time, NiSe2 itself is also unstable. Therefore, it is of great significance to develop a simple and low-toxic process to prepare NiSe2@C photocatalysts with excellent performance. Summary of the invention
[0005] The main purpose of the present invention is to provide a carbon-coated NiSe2 composite nanomaterial and a preparation method thereof, so as to overcome the deficiencies in the prior art.
[0006] Another object of the present invention is to provide an application of the carbon-coated NiSe2 composite nanomaterial.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] The embodiment of the present invention provides a method for preparing a carbon-coated NiSe2 composite nanomaterial, which comprises:
[0009] By adopting the chemical vapor transport method, a selenium source and nickel acetylacetonate as a carbon source and a nickel source are mixed and reacted in a vacuum environment to obtain a carbon-coated NiSe2 composite nanomaterial.
[0010] The embodiment of the present invention further provides a carbon-coated NiSe2 composite nanomaterial prepared by the above-mentioned preparation method, which includes NiSe2 and a carbon layer coated on the surface of NiSe2.
[0011] The embodiment of the present invention also provides the use of the carbon-coated NiSe2 composite nanomaterial in the preparation of a photocatalyst.
[0012] Compared with the prior art, the beneficial effects of the present invention are:
[0013] The raw materials selected from the preparation method of the carbon-coated NiSe2 composite nanomaterial provided by the present invention are selenium powder and nickel acetylacetonate, which greatly reduces the cost compared with traditional hydrogen production catalysts. The selenium source is selenium powder, which has low toxicity and high safety. In addition, the preparation process of the present invention is prepared in one step by chemical vapor transport, and the process is simple and easy to prepare. The obtained carbon-coated NiSe2 composite nanomaterial has been optimized in growth factors, has a uniform structure, and has good environmental stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 It is a schematic diagram of the preparation process of a carbon-coated NiSe2 composite nanomaterial in a typical embodiment of the present invention.
[0016] Figure 2a and Figure 2b These are the SEM images and EDS images of a carbon-coated NiSe2 composite nanomaterial in a typical embodiment of the present invention.
[0017] Figure 3 This is an XRD spectrum of a carbon-coated NiSe2 composite nanomaterial in a typical embodiment of the present invention.
[0018] Figure 4 This is a microscopic morphology of the Ni3Se2 material obtained in Example 1.
[0019] Figure 5 This is a microscopic morphology of the NiSe2 material obtained in Example 4.
[0020] Figure 6 This is a diagram of the catalytic performance of a carbon-coated NiSe2 composite nanomaterial in a typical embodiment of the present invention. DETAILED DESCRIPTION
[0021] In view of the defects of the prior art, the inventors of this case, after long-term research and extensive practice, were able to propose the technical solution of the present invention, which mainly adopts a one-step chemical vapor transport method to synthesize carbon-coated NiSe2 composite nanomaterials (hereinafter also referred to as "NiSe2@C materials").
[0022] The technical solution, its implementation process and principle are further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here.
[0023] As one aspect of the technical solution of the present invention, a method for preparing a carbon-coated NiSe2 composite nanomaterial involves: using a chemical vapor transport method to mix a selenium source and nickel acetylacetonate as a carbon source and a nickel source in a vacuum environment, and reacting them to obtain a carbon-coated NiSe2 composite nanomaterial ("NiSe2@C material").
[0024] As one of the preferred solutions, the selenium source includes selenium powder, which is low in toxicity and high in safety.
[0025] As one of the preferred solutions, the mass ratio of the nickel acetylacetonate to the selenium source is 1:2.
[0026] As one of the preferred solutions, the reaction temperature is 420-450° C. and the reaction time is 24-48 hours.
[0027] As one of the preferred solutions, the vacuum degree of the vacuum environment is less than 5×10 -3 Pa.
[0028] As one of the more preferred embodiments, please refer to Figure 1 As shown, the preparation method of the carbon-coated NiSe2 composite nanomaterial specifically includes:
[0029] Selenium powder (Se powder) and nickel acetylacetonate (Ni(acac)2) were mixed in a reaction chamber and ground thoroughly. After vacuum treatment, the reaction chamber was vacuum sealed to make the vacuum degree in the reaction chamber less than 5×10 -3 Pa, and then react at 420-450°C for 24-48h to obtain carbon-coated NiSe2 composite nanomaterials.
[0030] Another aspect of the embodiments of the present invention further provides a carbon-coated NiSe2 composite nanomaterial prepared by the aforementioned preparation method, which includes NiSe2 and a carbon layer coated on the surface of NiSe2.
[0031] Furthermore, the content of NiSe2 in the carbon-coated NiSe2 composite nanomaterial is 62-64wt%, and the content of carbon is 36-38wt%.
[0032] Furthermore, the thickness of the carbon layer is 10-20 nm.
[0033] The carbon-coated NiSe2 composite nanomaterial obtained by the invention has been optimized in growth factors, has a uniform structure and good environmental stability.
[0034] Another aspect of the embodiments of the present invention further provides the use of the aforementioned carbon-coated NiSe2 composite nanomaterial in the preparation of a photocatalyst.
[0035] Through the above technical scheme, the present invention selects selenium powder with lower toxicity as the selenium source, nickel acetylacetonate as the nickel source and the coated carbon source, and after exploring and optimizing the growth conditions of NiSe2 (raw material ratio, temperature, time and other factors), successfully prepares carbon-coated NiSe2 composite nanomaterials. The preparation process is prepared in one step by chemical vapor transport method, and the process is simple and easy to prepare.
[0036] In order to make the purpose, technical solution and application of the present invention clearer, the technical solution of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs, and the unspecified implementation conditions are usually the conditions in conventional experiments.
[0037] Example 1
[0038] like Figure 1 As shown, the preparation process of the carbon-coated NiSe2 composite nanomaterial ("NiSe2@C material") in this embodiment uses selenium powder as a selenium source, Ni(acac)2 (nickel acetylacetonate) as a carbon source and a nickel source, and a one-step chemical vapor transport method is used to synthesize the carbon-coated NiSe2 powder. The specific steps are as follows:
[0039] First, 100 mg of selenium powder and 50 mg of Ni(acac)2 were mixed, fully ground in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 450 °C for 24 hours and then cooled naturally to synthesize NiSe2@C material in one step by chemical vapor transport.
[0040] The SEM images and EDS images of the carbon-coated NiSe2 composite nanomaterial obtained in this example are shown in Figure 2. Figure 2a and Figure 2b As shown, the XRD spectrum is Figure 3 The catalytic performance is shown in Figure 6 shown.
[0041] After exploration and optimization, the inventors of this case found that the best growth conditions were a ratio of nickel acetylacetonate to selenium powder of 1:2 and a vacuum degree of less than 5×10 -3 Pa, kept at 450℃ for 24 hours.
[0042] Example 2
[0043] First, 100 mg of selenium powder and 50 mg of Ni(acac)2 were mixed, fully ground in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 420 °C for 48 hours and then cooled naturally to synthesize NiSe2@C material in one step by chemical vapor transport.
[0044] Example 3
[0045] First, 100 mg of selenium powder and 50 mg of Ni(acac)2 were mixed, fully ground in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 430 °C for 36 hours and then cooled naturally to synthesize NiSe2@C material in one step by chemical vapor transport.
[0046] After testing, the structural morphology and catalytic performance of the carbon-coated NiSe2 composite nanomaterials obtained in Examples 2 and 3 are basically consistent with those of the product in Example 1.
[0047] Comparative Example 1
[0048] 100 mg of selenium powder and 100 mg of Ni(acac)2 were mixed, ground thoroughly in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 450°C for 24 hours and then cooled naturally to synthesize Ni3Se2 without forming a carbon coating structure. The product morphology is as follows Figure 4 As shown, from Figure 4 From the SEM image, it can be seen that the reason why the carbon coating structure is not formed may be that the carbon content is insufficient after Ni(acac)2 and Se powder fully react.
[0049] Comparative Example 2
[0050] 100 mg of selenium powder and 75 mg of Ni(acac)2 were mixed, ground thoroughly in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 400°C for 24 hours and then cooled naturally to synthesize NiSe. The reason is that different proportions of Ni(acac)2 and Se will cause different reactions, resulting in different products.
[0051] Comparative Example 3
[0052] 100 mg of selenium powder and 50 mg of Ni(acac)2 were mixed, ground thoroughly in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 400°C for 24 hours and then cooled naturally to synthesize Ni 0.85 Se.
[0053] Comparative Example 4
[0054] 100 mg of selenium powder and 50 mg of Ni(acac)2 were mixed, ground thoroughly in an agate mortar, and then transferred to a quartz tube. After that, the quartz tube was vacuum-sealed after repeated high vacuum treatment, with a vacuum degree of less than 5×10 -3 The quartz tube was placed in a furnace at 500°C for 24 hours and then cooled naturally to generate NiSe2. However, because the reaction temperature was too high, the product morphology was a mixture of needles and blocks, such as Figure 5 shown.
[0055] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0056] It should be understood that the above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon-coated NiSe2 composite nanomaterial, characterized in that: include: The carbon-coated NiSe2 composite nanomaterial is obtained by mixing a selenium source and nickel acetylacetonate as a carbon source and a nickel source in a vacuum environment by chemical vapor transport method. The vacuum degree of the vacuum environment is less than 5×10 -3 Pa, the reaction temperature is 420-450°C, the reaction time is 24-48h, the mass ratio of the nickel acetylacetonate to the selenium source is 1:2; the selenium source is selenium powder; The carbon-coated NiSe2 composite nanomaterial comprises NiSe2 and a carbon layer coated on the surface of NiSe2. The content of NiSe2 in the carbon-coated NiSe2 composite nanomaterial is 62-64wt%, and the content of carbon is 36-38wt%.
2. The preparation method according to claim 1, characterized in that: Specifically include: Selenium powder and nickel acetylacetonate were mixed in a reaction chamber and fully ground. After vacuum treatment, the reaction chamber was vacuum sealed to make the vacuum degree in the reaction chamber less than 5×10 -3 Pa, and then react at 420-450 °C for 24-48 h to obtain carbon-coated NiSe2 composite nanomaterials.
3. A carbon-coated NiSe2 composite nanomaterial prepared by the preparation method according to any one of claims 1-2, comprising NiSe2 and a carbon layer coated on the surface of NiSe2, wherein the content of NiSe2 in the carbon-coated NiSe2 composite nanomaterial is 62~64wt%, and the content of carbon is 36~38wt%.
4. The carbon-coated NiSe2 composite nanomaterial according to claim 3, characterized in that: The thickness of the carbon layer is 10-20 nm.
5. Use of the carbon-coated NiSe2 composite nanomaterial according to any one of claims 3 to 4 in the preparation of photocatalysts.
Citation Information
Patent Citations
Preparation method and application of flowerlike structure NiSe<2>
CN110823971A
Transition metal chalcogen-group carbon-based heterostructure composite material with regular morphology and preparation method and application of transition metal chalcogen-group carbon-based heterostructure composite material
CN110683522A